2007
DOI: 10.1007/s11705-007-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of statistical thermodynamic model for binary protein adsorption equilibria on cation exchange adsorbent

Abstract: knowledge of mass transfer kinetics is required to optimize the chromatographic purification process, as the process performance is mass-transfer-limited in many applications. Liquid chromatography models on the basis of continuity equations are useless unless they are fed with appropriate adsorption isotherm equations, describing the basic thermodynamic equilibria between biomolecules in the mobile phase and the stationary phase. Therefore the study of adsorption equilibrium is of major importance for liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Recently, we have applied the model to the adsorption of BSA and Hb to a cation exchanger and investigated the influence pH (pH 4.5-5.5) on the adsorption of the same binary protein system (23). It was shown that the model prediction agrees with the experiments reasonably well.…”
Section: St Model Parameters For Single-component Adsorptionmentioning
confidence: 91%
“…Recently, we have applied the model to the adsorption of BSA and Hb to a cation exchanger and investigated the influence pH (pH 4.5-5.5) on the adsorption of the same binary protein system (23). It was shown that the model prediction agrees with the experiments reasonably well.…”
Section: St Model Parameters For Single-component Adsorptionmentioning
confidence: 91%